Table 2_Global burden of hearing loss in people aged 60 years and older, 1990–2021: results from the global burden of disease study.xlsx - Zhi-qiang Zhang (4587796) (2025)
Background Hearing loss (HL) is a significant public health concern, particularly among older adults, where it ranks as the third most common cause of years lived with disability (YLD) globally. This study aims to comprehensively analyze the burden of HL among individuals aged 60 years and older from 1990 to 2021, utilizing data from the Global Burden of Disease (GBD) database. Methods We employed a variety of analytical approaches, including descriptive analysis, Joinpoint regression, age-period-cohort analysis, decomposition analysis, and predictive modeling. The study examined trends in incidence, prevalence, and disability-adjusted life years (DALYs) across different socio-demographic index (SDI) quintiles, regions, and genders. Results Our findings reveal significant increases in age-standardized rates (ASR) of HL and YLDs over the study period (EAPC = 0.13 and 0.14, respectively), with notable disparities across SDI categories. The burden of HL was highest in low SDI countries, where socio-economic factors severely impacted access to hearing care. Gender differences were pronounced, with males exhibiting higher prevalence rates than females. Predictive analysis indicates a continued rise in HL cases and associated YLDs (projected to reach 46.9 million YLDs by 2040), emphasizing the urgent need for targeted public health interventions. Conclusion The increasing burden of HL among older adults necessitates enhanced awareness, early detection, and improved access to hearing care services, particularly in low and middle-income countries. Addressing these disparities is crucial for mitigating the socio-economic impacts of HL and improving the quality of life for affected individuals.